2009
DOI: 10.4040/jkan.2009.39.4.518
|View full text |Cite
|
Sign up to set email alerts
|

A Prediction Model Development on Quality of Life in Kidney Transplant Recipients

Abstract: Purpose:The purpose of this study was to identify factors influencing quality of life in kidney transplant recipients and to understand the concrete pathway of influence and the power of each variable, so that integrated prediction model to promote the quality of life of kidney transplant recipients could be developed. Methods: The sample was composed of 218 patients in follow-up care after a kidney transplant in one of 4 university hospitals in the Honam area. A structured questionnaire was used and the colle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 12 publications
2
6
0
2
Order By: Relevance
“…We found that compliance and side effects were associated with very low scores [51], in every dimension and regardless of the measurement instrument used [52-54]. These results could be explained by the lack of information received concerning possible side effects, and the extreme importance of the treatment schedule [55].…”
Section: Resultsmentioning
confidence: 99%
“…We found that compliance and side effects were associated with very low scores [51], in every dimension and regardless of the measurement instrument used [52-54]. These results could be explained by the lack of information received concerning possible side effects, and the extreme importance of the treatment schedule [55].…”
Section: Resultsmentioning
confidence: 99%
“…Основываясь на данных работы [24], в которой мето-дом фотолюминесцентной спектроскопии были изучены образцы GaAs с различным уровнем легирования маг-нием, и сравнивая их с нашими результатами, можно утверждать, что, исходя из формы полосы фотолю-минесценции гетероструктур, количество введенных в твердый раствор атомов примеси соответствует уровню легирования ∼ 10 18 см −3 . Этот результат согласуется с данными, полученными методами высокоразрешающей дифракции и рамановской спектроскопии.…”
Section: фотолюминесцентная спектроскопияunclassified
“…Среди возможных вариантов наиболее перспективным является магний [19][20][21]. Использова-ние Mg весьма предпочтительно, так как он имеет большую растворимость и, встраиваясь в катионные узлы твердых растворов на основе A III B V , представ-ляет собой неглубокий акцепторный уровень [22][23][24][25]. Кроме того, легированные магнием эпитаксиальные слои имеют более низкое удельное сопротивление при аналогичном составе, нежели при использовании ана-логичных примесей для создания p-типа легирующей примеси.…”
Section: Introductionunclassified
“…To date, the existing cancer interventions have focused mainly on physical and psychological symptoms and QOL for cancer patients; a few studies have focused on how to improve self‐efficacy for cancer survivors . Studies revealed that self‐efficacy is a strong predictor of QOL for cancer patients and other disease populations, such as kidney transplant patients and coronary heart disease . In this study, we use Bandura's Social Cognitive Theory to guide and design the rehabilitation programme.…”
Section: Introductionmentioning
confidence: 99%